The binding of negative emotional stimuli with spatial information in working memory: A possible role for the episodic buffer - Cianfanelli, Beatrice; Esposito, Antonino; Spataro, Pietro; Santirocchi, Alessandro; Cestari, Vincenzo; Rossi-Arnaud, Clelia; Costanzi, Marco (Frontiers in Neuroscience, 2023)
Introduction Remembering where negative events occur has undeniable adaptive value, however, how these memories are formed remains elusive. We investigated the role of working memory subcomponents in binding emotional and visuo-spatial information using an emotional version of the object relocation task (EORT). Methods After displaying black rectangles simultaneously, emotional pictures (from the International Affective Pictures System) appeared sequentially over each rectangle. Participants repositioned the rectangles as accurately as possible after all stimuli had disappeared. During the EORT encoding phase, a verbal trail task was administered concurrently to selectively interfere with the central executive (CE). The immediate post-encoding administration of an object feature-report task was used to interfere with the episodic buffer (EB). Results Only the EB-interfering task prevented the emotion-enhancing effect of negative pictures. The latter effect was not observed with a concurrent executive task. Discussion Overall, our findings suggest that pre-attentive automatic processes are primarily involved in binding emotional and visuo-spatial information in the EB.